Criminal Attacks on Schools and Colleges in Nigeria: What Implications for Educational Development in Niger State, Nigeria - Ibrahim Ishola Yahaya (GREAT : Journal of Global Economic Trends, 2026)
Education plays a critical role in human capital development, social transformation, and sustainable national development. However, increasing criminal attacks on schools and colleges in Nigeria, particularly in Niger State, have emerged as a major threat to educational access, quality, and continuity. Recurrent incidents of school kidnappings, banditry, and violent attacks have disrupted academic activities, created fear among learners and parents, and undermined educational development in affected communities. This study examined the factors responsible for criminal attacks on schools and colleges in Niger State and analysed their implications for educational development. The study adopted a qualitative research approach based on documentary analysis. Secondary data were obtained from peer-reviewed journal articles, government publications, policy documents, reports of international organisations, security reports, and credible media sources. The data were analysed using thematic content analysis and interpreted through the lens of State Fragility Theory. The findings revealed that criminal attacks on schools are driven by socioeconomic deprivation, youth unemployment, governance and security failures, deliberate targeting by organised criminal networks, the vulnerability of rural and boarding schools, and the proliferation of small arms. The study further found that these attacks have resulted in school closures, declining enrolment, increased numbers of out-of-school children, teacher shortages, psychosocial trauma, and deterioration in educational quality. The attacks also undermine human capital development and reinforce cycles of poverty and underdevelopment. The study concludes that criminal attacks on schools constitute both a security and developmental challenge.